Molecular biology of pancreatic neuroendocrine tumors: From mechanism to translation - Shen, Xiaofei; Wang, Xingzhou; Lu, Xiaofeng; Zhao, Yang; Guan, Wenxian (Frontiers in Oncology, 2022)
Pancreatic neuroendocrine tumors (pNETs) are a group of heterogeneous tumors originated from progenitor cells. As these tumors are predominantly non-functional, most of them display asymptomatic characteristics, making it difficult to be realized from early onset. Therefore, patients with pNETs are usually diagnosed with metastatic disease or at a late disease stage. The relatively low incidence also limits our understanding of the biological background of pNETs, which largely impair the development of new effective drugs. The fact that up to 10% of pNETs develop in patients with genetic syndromes have promoted researchers to focus on the gene mutations and driver mutations in MEN1, DAXX/ATRX and mTOR signaling pathway genes have been implicated in disease development and progression. Recent advances in sequencing technologies have further enriched our knowledge of the complex molecular landscape of pNETs, pointing out crucial roles of genes in DNA damage pathways, chromosomal and telomere alterations and epigenetic dysregulation. These novel findings may not only benefit early diagnosis of pNETs, but also help to uncover tumor heterogeneity and shape the future of translational medical treatment. In this review, we focus on the current molecular biology of pNETs and decipher how these findings may translate into future development of targeted therapy.